PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER DAN MORAL SISWA DI ERA DIGITAL - Nabila Mulyanti; Muhammad Rendy Firdaus; M Al Fadly; Rika Istiani; Raka Shiwie D'Amore Firdaus; Mukhtar Latif (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Character and moral degradation among students in the digital era has become a growing concern in Islamic education, as unrestricted access to information and social media exposes learners to values that often contradict Islamic teachings. This study aims to describe the role of Islamic Religious Education (PAI) teachers in shaping the character and moral values of students amid the challenges and opportunities offered by digital technology. This research employs a qualitative approach using the literature study method, in which data were collected from relevant scientific journal articles and books published within the last five years, then selected, categorized, and synthesized to answer the research problem. The findings show that PAI teachers play multiple interrelated roles, namely as moral exemplars (uswah hasanah), spiritual guides (murabbi), and facilitators of religious digital literacy who direct students toward the wise use of technology. Strategies commonly applied include habituating daily worship, integrating Islamic values into contextual and technology-based learning, and building close personal communication with students to reinforce religious character amid digital distraction. This study concludes that the strategic role of PAI teachers remains essential and needs to be strengthened through continuous digital competency training so that character education can adapt without losing its spiritual orientation.